House of the red fish - Salisbury, Graham (Ember, 2014)
Over a year after Japan's attack on Pearl Harbor and the arrest of Tomi's father and grandfather, Tomi and his friends, battling anti-Japanese-American sentiment in Hawaii, try to find a way to salvage his father's sunken fishing boat.